A Few More Words about Beowulf - Busbee, Mark Bradshaw (Grundtvig-Studier, 2016)
In September of 1815, Grundtvig published his second article about Beowulf, “Nok et Par Ord om Bjovulfs Drape” [A Few More Words about the Heroic Poem of Beowulf] in Nyeste Skilderie af Kjøbenhavn [The Latest Scenes ofCopenhagen].i The article was intended to end once and for all the literary feud that had developed between him, Grímur Jónson Thorkelin, who had published the first modern edition of Beowulf, and Peter Erasmus Müller, who had anonymouslyreviewed the edition.ii The article is notable for two main reasons: first, it reveals Grundtvig far ahead of his contemporaries as a scholar of the poem and,second, it displays in full Grundtvig’s aggressive tone when in the heat of debate.